Hubungan Dukungan Keluarga Terhadap Tingkat Stigmatisasi pada Klien Skizofrenia di Panti Gramesia Kedawung - Riza Arisanty Latifah; Uus Husni Mahmud; Syekha Syekha (Jurnal Keperawatan Galuh, 2025)
Background: Stigmatization of schizophrenia impacts social acceptance of patients. Family support can be a buffer against the effects of stigma. Objective: To determine the relationship between stigmatization and family support in schizophrenia clients. Method: Quantitative research with a descriptive correlational design, with 51 respondents using accidental sampling. Analysis using the Fisher exact test. Results: The majority of respondents experienced moderate stigma (66.7%) and received good family support (72.5%). There was a significant relationship between stigmatization and family support (p = 0.007). Conclusion: Good family support is closely related to low levels of stigmatization in schizophrenia clients.